El techo de la ballena : retro-modernity in Venezuela - Gaztambide, María C. (Florida scholarship online., 2019)
In this volume, María C. Gaztambide presents an account of the visual arts production of the Caracas-based collective El Techo de la Ballena (active 1961-69).